A memória das cidades na sociedade digital: reflexões para São Paulo e o exemplo de ‘Quando a cidade era mais gentil’ - Martin Jayo; Diego Vasconcellos Vargas (Confins)
Two decades after its publication, the essay On the Memory of Cities, by geogragher Maurício de Almeida Abreu, preserves all its relevance and continues to be widely quoted and acknowledged. However, a relatively new and potentially important element, concerning discussions about the memory of cities, seems to be receiving less attention than it could: the way in which, in the context of society digitalization, information and communication technologies (ICT) might alter the forms through which the so-called urban memory can be built, transmitted and preserved. Starting from Abreu’s conceptual discussion, we argue in this article that São Paulo, due to its historical characteristics and its lack of places dedicated to memory, can be configured as a privileged laboratory for the experimentation of ICT as a support for this type of memory.